2016
DOI: 10.17323/1813-8918-2016-1-79-110
|View full text |Cite
|
Sign up to set email alerts
|

Отношение К Гомосексуалам В России: Содержание, Структура И Предикторы

Abstract: Despite the growth of negative attitudes to homosexuals in Russia the research into this topic has been extremely scarce. Based on the analysis of social discourse, we have created a pool of items and undertaken three empirical studies aimed to develop and validate the Russian Attitudes to Homosexuals Inventory (RAHI) and investigate the associations of homophobic attitudes with a range of demographic and psychological variables. In Study 1 we used an online sample (N = 1,007) and explored the structure of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 55 publications
(78 reference statements)
3
10
0
Order By: Relevance
“…People perception of homosexuals threats in this study has some similarities with Gulevich et al (2016) findings in Russian context. Russian people also considered homosexuals as a threat to the morality, deviating from the social norm, cannot be morally justified, and challenges the values and culture of society.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…People perception of homosexuals threats in this study has some similarities with Gulevich et al (2016) findings in Russian context. Russian people also considered homosexuals as a threat to the morality, deviating from the social norm, cannot be morally justified, and challenges the values and culture of society.…”
Section: Discussionsupporting
confidence: 83%
“…Another finding of this study that indicated no relationship between sex and perceived threat of homosexuals seems to be similar with Manalastas et al (2017) findings which showed that there was no difference in homonegativity by sex in Indonesia, Singapore, and Thailand. For the future research, it will be more interesting to use gender identity rather than sex as a predictor, because previous studies have shown that prejudice against homosexuals is generally found in men whose traditional masculine identification is very high (Gulevich et al, 2016). Homosexuals that are not in harmony with the standard role of masculinity will trigger anxiety and feeling threatened.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations